Alterations and Correlations of Gut Microbiota and Fecal Metabolome Characteristics in Experimental Periodontitis Rats - Wu, Lan; Han, Jie; Nie, Jia-Yan; Deng, Tong; Li, Cheng; Fang, Cheng; Xie, Wen-Zhong; Wang, Shuang-Ying; Zeng, Xian-Tao (Frontiers in Microbiology, 2022)
Objectives: Periodontitis affects the progression of many diseases, while its detailed mechanism remains unclear. This study hopes to provide new ideas for exploring its mechanism by analyzing the gut microbiota and fecal metabolic characteristics of experimental periodontitis rats. Methods: Ten rats were randomly divided into ligature-induced experimental periodontitis (EP) group and healthy control group. After 4 weeks of the experiment, the feces of all rats were collected for sequencing through 16S ribosomal RNA (rRNA) sequencing technology and liquid chromatography-mass spectrometry (LC-MS). Results: 16S rRNA sequencing results showed that the β-diversity of gut microbiota was significantly different between the EP and control group, and the levels of dominant genera were different. Compared with the control group, Ruminococcus, Escherichia and Roseburia were significantly enriched in EP, and Coprococcus, Turicibacter, Lachnospira were significantly decreased. Correlation analysis showed that Roseburia exhibited the highest correlation within the genus. Of 3488 qualitative metabolites, 164 metabolites were up-regulated and 362 metabolites were down-regulated in EP. Enrichment analysis showed that periodontitis significantly changed 45 positive/negative ion metabolic pathways. Five KEGG pathways, protein digestion and absorption, tyrosine metabolism, glycolysis/gluconeogenesis, niacin and nicotinamide metabolism, and oxidative phosphorylation, are enriched in both the microbiome and metabolome. Correlation analysis showed that the genera with significant differences in periodontitis were usually significantly correlated with more metabolites, such as Roseburia, Lachnospira, Escherichia, Turicibacter and Ruminococcus. The genera with the same changing trend tended to have the similar correlation with some certain metabolites. In addition, vitamin D2 and protoporphyrin IX have the most significant correlations with microorganisms. Conclusions: Our study reveals that periodontitis alters gut microbiota and fecal metabolites. The correlation analysis of microbiota and metabolome provides a deeper understanding of periodontitis, and also provides a direction for the study of periodontitis affecting other diseases.